Development of teamrole inventory for co-curriculum subjects - Mohd Azam, Muhammad Akhir; Mohd Ali, Zarina; Ahmad Fazullah, Mohd Zainal Abidin; Abdul Rani, Anita; Ramle, Abid; Nor Suhardiliana, Sahar (2008)
Teamworking is one of the seven elements of soft skills· identified by the Ministry of Higher Education (MoHE) deemed essential for students to have in order to become graduates who, upon graduation, possess the knowledge and towering personality to face current challenges. These skills have been applied in the teaching and learning process across the curriculum and in co-curriculum. Co-curriculum is one but relevant component which promotes the soft skills that help to complement the hard skills in the curriculum design and development process. As such, this study was designed with the aim of identifying types of teamroles among Universiti Malaysia Pahang (UMP) students taking compulsory co-curriculum course, the Briged Siswa. This study was based on the teamrole inventory developed by Be/bin in his Be/bin's Team Role Model. Sample consisted of 285 first year students. Researchers had translated and adapted Be/bin's teamrole inventory to suit local cultures and administered pre-test and post-test survey using this questionnaire, comprising 7 parts according to 8 types of teamroles. Data from the suvey were analysed using SPSS version 11.5 to determine the difference between pre-test and post-test. The Wilcoxon matched-pairs signed-ranks test, a nonparametric method, was used to determine the difference between the two. Results from statistical analysis showed that there existed mixed variations of percentage of teamrole typology in relation to the research setting and from the context of the content delivery and implementation of the Briged Siswa mo_dule. It was also discovered that there was no significant difference in pre-test and post-test of all eight teamroles that existed among UMP students taking the course. Nevertheless, the study has provided insights into the development of a more comprehensive assessment and evaluation system, moving towards developing teamrole inventory for co-curriculum subjects for UMP engineering undergraduates and contributed to the literature in soft skills enhancement among students.